(untitled) (PerCursos, 2010)
Este artigo pretende discutir a produção de livros didáticos de História do Brasil no período imperial brasileiro e sua ligação com a inventividade do sentimento nacional. Os autores desses manuais eram, em sua maioria, sócios do Instituto Histórico e Geográfico Brasileiro (IHGB) e/ou professores do Colégio Pedro II. Portanto, falavam de um lugar-social bastante específico, possuindo, muitas vezes, estreitas ligações com os poderes institucionais. Com as instabilidades da Regência, o IHGB assumiu a função de criar uma legitimidade para a unidade nacional. Assim, o livro didático de história pátria assume também esse papel, sobretudo junto à mocidade brasileira, estabelecendo, com isso, uma verdadeira “pedagogia do cidadão”. Palavras-Chave: Historiografia brasileira. Brasil Império. Abstract The purpose of this article is to discuss the production of didactic books of the History of Brazil in the period of the Brazilian Empire and its association with the inventiveness of the national sentiment. Most of the authors of these manuals were partners of the Brazilian Historical and Geographical Institute (IHGB) and/or teachers of Colégio Pedro II (school). Therefore, they spoke about a very specific social place, many times, with close relations with the institutional powers. With the instabilities of the Regency Era, the IHGB took on the role of creating legitimacy to the national unit. Thus, the didactic book of the homeland History also took on this role, especially among the Brazilian youth, thus, establishing a real “pedagogy of the citizen”. Key Words: Teaching History. Didactic book. Invention of nationality. Brazilian Historiography. Brazilian Empire.